2020
DOI: 10.1136/annrheumdis-2020-217834
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association of phenotypes based on clustering patterns of hand osteoarthritis identifyWNT9Aas novel osteoarthritis gene

Abstract: BackgroundDespite recent advances in the understanding of the genetic architecture of osteoarthritis (OA), only two genetic loci have been identified for OA of the hand, in part explained by the complexity of the different hand joints and heterogeneity of OA pathology.MethodsWe used data from the Rotterdam Study (RSI, RSII and RSIII) to create three hand OA phenotypes based on clustering patterns of radiographic OA severity to increase power in our modest discovery genome-wide association studies in the RS (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 51 publications
(51 reference statements)
0
34
0
4
Order By: Relevance
“…There are three main mechanisms of epigenetic regulation of gene expression: post-translational modification of histones, noncoding RNAs (ncRNAs, such as miRNAs), and DNAm, of which the latter is the most well-studied. Studies of the cartilage DNA methylome have led to the discovery of OA-associated methylation quantitative trait loci (mQTLs), at which there is a correlation between genotype at an OA risk SNP and cis DNAm 25,54,63,64 . DNAm is thought to act as a conduit through which the functional effect of A STRING proteineprotein interaction network of OA risk gene products.…”
Section: Interaction Between Oa Genetics and Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three main mechanisms of epigenetic regulation of gene expression: post-translational modification of histones, noncoding RNAs (ncRNAs, such as miRNAs), and DNAm, of which the latter is the most well-studied. Studies of the cartilage DNA methylome have led to the discovery of OA-associated methylation quantitative trait loci (mQTLs), at which there is a correlation between genotype at an OA risk SNP and cis DNAm 25,54,63,64 . DNAm is thought to act as a conduit through which the functional effect of A STRING proteineprotein interaction network of OA risk gene products.…”
Section: Interaction Between Oa Genetics and Epigeneticsmentioning
confidence: 99%
“…DOT1L expression is essential for cartilage homeostasis, and the identification of this region as a risk locus strongly supports the requirement for tight regulation of chromatin state to maintain cartilage integrity 62 . Similarly, OA risk SNPs have been identified in the region of cartilage-specific ncRNAs that are known to be vital for homeostasis of the articular joint surface and are dysregulated in OA, including the miRNAs miR-140 and miR-455 23,25 .…”
Section: Table IIImentioning
confidence: 99%
“…Due to the genetic complexity of the reported regions, the identification of functional SNPs and effector genes at the majority of OA risk loci remains elusive (16,17). In recent years, post-GWAS | 1857 integration of epigenetic data sets has increasingly been conducted to colocalize genetic risk loci with changes to the cartilage epigenome (18)(19)(20)(21). Correlations between genotypes at OA association SNPs and DNA methylation have been identified in cartilage, marking methylation quantitative trait loci (QTLs) (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Current GWAS have included thousands of patients with OA 21,23,67 , but a full metaanalysis of multiple populations will likely lead to the identification of further risk variants. This year Boer et al, elegantly demonstrated how analysis of well-characterized patient cohorts, where patients were segregated into distinct disease sub-types (in this case of hand OA), could increase the discovery power of a relatively modestly sized GWAS 15 . An expectation in the coming year(s) would be that further patient or disease stratification could improve GWASderived knowledge of disease-associated loci for OA of the other joint sites.…”
Section: Future Approaches and Summarymentioning
confidence: 99%